A DC-DC converter for bipolar DC microgrids with voltage balance capability to supply a multilevel SRM drive - Fernão Pires, V. (2021)
In this work it is proposed a DC-DC converter to supply a multilevel Switched Reluctance Machine (SRM) drive. The proposed converter was designed to be integrated in a bipolar DC microgrid. Usually, this kind of microgrid requires a support to avoid unbalances between the poles. Thus, the proposed converter also integrates voltage balance capabilities allowing the required support to the bipolar DC microgrid. Besides that, the converter can also supply the drive using only one of the poles. The behavior and operating modes of the converter will be described in detail. Several simulation tests will also be provided. From these tests, the behavior and the several operation modes of the DC-DC as well as the multilevel SRM drive supplied by this converter will also be presented and analyzed.